Evaluation of ergonomics conditions in works in university restaurants - Schneider, Nicole; Strasburg, Virgílio José (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The activities for the production and supply of meals should consider aspects related to the health of workers. The goal of this study was to identify work conditions in distribution and sanitizing of utensils in the University Restaurants (URs). A descriptive cross-sectional observational study has been conducted in two URs of the public federal university in Porto Alegre / RS. Differences were found in the weight of the tanks -of 6,9kg to 22,4kg -according to the type of preparation and of the number of replacements of the distribution activities. The staff performed repetitive stress without function changingin the distribution and with a maximum of 20% exchange in the laundry during the period of 2 hours and 30 minutes. The ambient temperature of laundry (cleaning utensils) exceeded the recommended values and the noise reached almost the limit. Regarding the use of personal protectiveequipment (PPE) workers did not use hearing protection, but made use of boots. The physical structure has contributed to the founded results.